2019
DOI: 10.26666/rmp.ijbm.2019.5.1
|View full text |Cite
|
Sign up to set email alerts
|

The determinants factors of accounting practitioner’s attitude towards the use of Malaysian Business Reporting System (MBRS)

Abstract: MBRS is a new submission platform introduce by SSM that enable the submission filings in XBRL format in Malaysia. However, since the introducing of SSMxT in 2014, the issue of XBRL format adoption by companies in Malaysia is still questionable especially regarding the attitude of potential users towards the use of XBRL format. Therefore, this study is try to examine factors of user attitude towards the use of MBRS. Accounting practitioners has been choose as unit analysis of this study. The data was collect ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…There is a significant positive influence between perceived ease of use (PEOU) and the intention to use (ITU) MBRS in Malaysia. Chouhan and Goswami (2015) found that perceived ease of use and perceived usefulness had a positive impact on attitudes towards using XBRL, supported by Uyob et al (2019aUyob et al ( , 2019b (study before the implementation of MBRS). However, the results could be different after MBRS implementation.…”
Section: Perceived Usefulnessmentioning
confidence: 85%
See 3 more Smart Citations
“…There is a significant positive influence between perceived ease of use (PEOU) and the intention to use (ITU) MBRS in Malaysia. Chouhan and Goswami (2015) found that perceived ease of use and perceived usefulness had a positive impact on attitudes towards using XBRL, supported by Uyob et al (2019aUyob et al ( , 2019b (study before the implementation of MBRS). However, the results could be different after MBRS implementation.…”
Section: Perceived Usefulnessmentioning
confidence: 85%
“…The Companies Commission of Malaysia (CCM) has started using XBRL to speed up the company filing process. To improve the efficiency and effectiveness of filing processes by leveraging the XBRL format, the Malaysian business reporting system (MBRS) was launched by CCM in September 2018 (Uyob et al, 2019a(Uyob et al, , 2019b. It solves significant challenges such as insufficient physical storage capacity, lengthy procedures, human error, delay and missing physical documentation [Companies Commission of Malaysia (CCM), 2019].…”
Section: Malaysia Business Reporting Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Investors and analysts on the other hand, can easily compare companies and industries across time by using XBRL (Ling, 2019). This consistent tag technology can standardize a report and enable it to communicate with wide range of electronic devices (Tohang & Lan, 2017;Uyob et al, 2019a). As a result, XBRL is able to contribute key qualitative characteristics of meaningful financial accounting information by providing a comparison element (IFRS, 2018).…”
Section: The Popularity Of Xbrlmentioning
confidence: 99%